Preparation of Resistant Starch by Ultrasonic Annealing Method and Its Physicochemical Properties - Xurui ZENG; Liangzhong LIU; Ting QI; Zhe ZHU (Shipin gongye ke-ji, 2023)
In order to optimize the process conditions for the preparation of waxy rice resistant starch by ultrasonic annealing method, this study took the content of resistant starch as an index, and based on the single factor experiment, the response surface analysis method was used to explore the effects of water content, ultrasonic time, annealing temperature and annealing time on the content of resistant starch, and the physicochemical properties of the prepared resistant starch were analyzed. The results showed that the optimum conditions were as follows: Water content 68%, ultrasonic time 23 min, annealing temperature 55 ℃, annealing time 25 h. Under these conditions, the content of resistant starch was 45.61%±0.95%. Compared with original starch, the transparency of waxy rice resistant starch increased by 38.19%, and the solubility at 90 ℃ increased from 6.03% to 52.45%, while the swelling power decreased from 41.04 g/g to 6.38 g/g. Under scanning electron microscope, the surface morphology of resistant starch changed significantly, which showed that it was a rough structure with many holes. Fourier infrared spectroscopy showed that ultrasonic annealing promoted the generation of short-range ordered structures of starch. Differential scanning calorimetry analysis showed that the enthalpy of resistant starch increased by 5.05 J/g after ultrasonic annealing, and X-ray diffraction analysis displayed that the crystalline shape was changed and the crystallinity of resistant starch was improved. This study provided a reference for the industrial production of waxy rice resistant starch.